Enhancing Oxygen Reduction Activity of Pt‐based Electrocatalysts: From Theoretical Mechanisms to Practical Methods - Ma, Zhong; Cano, Zachary P.; Yu, Aiping; Chen, Zhongwei; Jiang, Gaopeng; Fu, Xiaogang; Yang, Lin; Wu, Tianpin; Bai, Zhengyu; Lu, Jun (Angewandte Chemie (International ed.), 2020)
Pt‐based electrocatalysts are considered as one of the most promising choices to facilitate the oxygen reduction reaction (ORR), and the key factor enabling their success is to reduce the required amount of platinum. Herein, we focus on illuminating both the theoretical mechanisms which enable enhanced and sustained ORR activity and the practical methods to achieve them in catalysts. The various multi‐step pathways of ORR are firstly reviewed and the rate‐determining steps based on the reaction intermediates and their binding energies are analyzed. We then explain the critical aspects of Pt‐based electrocatalysts to tune oxygen reduction properties from the viewpoints of active sites exposure and altering the surface electronic structure, and further summarize representative research progress towards practically achieving these activity enhancements with a focus on platinum size reduction, shape control and core Pt elimination methods. We finally outline the remaining challenges and provide our perspectives with regard to further enhancing their activities. Pt‐based electrocatalysts: This Minireview illuminates both the theoretical mechanisms from the viewpoints of active sites exposure and altering the surface electronic structure, which enable enhanced and sustained ORR activity, and the practical methods to achieve them in catalysts, with a focus on size reduction, shape control and core elimination methods.